(untitled) (Cadernos de Sociomuseologia, 2017)
This paper reserves to show the ex-voto, object placed by the religiousness act in Catholic sanctuary, in particular, in the halls of miracles. Here, an excerpt Productions Project Ex-votos from Brazil: Step museums, linked to CNPq, which reached in museums and the halls of miracles of 17 Brazilian states, and in some regions of Portugal, spaces devoted to heritage worship which bring, among its riches, the testimonial nature of faith, and present stories of lives portrayed in media pictorial, photographic, tickets, sculptures, objects, organic and industrial objects, presenting situations that reflect individual and collective values ​​in economic, social, educational, the health, fear, pleasure, happiness, sadness, short, situations that, in addition to specifying the nature of the individual enhances social memory local, regional and national levels, which stemmed from Portugal in Brazil, which today shows a continuous and rich tradition. Keywords: Ex-votos, religiosity, cultural patrimony, lusofony.